2022
DOI: 10.3390/molecules27217574
|View full text |Cite
|
Sign up to set email alerts
|

Improved Adsorption of the Toxic Herbicide Diuron Using Activated Carbon Obtained from Residual Cassava Biomass (Manihot esculenta)

Abstract: The production and consumption of cassava (Manihot esculenta) occur in several places worldwide, producing large volumes of waste, mostly in the form of bark. This study sought to bring a new purpose to this biomass through producing activated carbon to use as an adsorbent to remove the herbicide Diuron from water. It was observed that the carbon contains the functional groups of methyl, carbonyl, and hydroxyl in a strongly amorphous structure. The activated carbon had a surface area of 613.7 m2 g−1, a pore vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 84 publications
0
5
0
1
Order By: Relevance
“…This result agrees with other research using ZnCl2 in proportions of 1:1. The biomasses used in this study were: jabuticaba residues [44], açai residues [45], fruits of the invasive species Hovenia dulcis [46] and cassava peels [47]. When using KOH as an activating agent, the authors reported a yield close to 64% [48].…”
Section: Characterization Results Of the Source And Pyrolyzed Materialsmentioning
confidence: 94%
“…This result agrees with other research using ZnCl2 in proportions of 1:1. The biomasses used in this study were: jabuticaba residues [44], açai residues [45], fruits of the invasive species Hovenia dulcis [46] and cassava peels [47]. When using KOH as an activating agent, the authors reported a yield close to 64% [48].…”
Section: Characterization Results Of the Source And Pyrolyzed Materialsmentioning
confidence: 94%
“…The resulting carbonaceous skeleton, composed mainly of carbon, exhibited a yield of approximately 27%, consistent with previous studies using a 1:1 proportion of ZnCl 2 . The four biomasses examined in this investigation were Jabuticaba residues [ 34 ], açai residues [ 35 ], Hovenia dulcis fruits [ 27 ], and cassava peels [ 36 ]. The authors reported a yield of about 64 % when KOH was used as the activating agent [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…ln q e = ln K F + (1∕n) ln C e (6) q e : adsorption capacity at equilibrium, in mg g −1 ; C e : the concentration of adsorbate at equilibrium, in mg L −1 ; K F and n are Freundlich parameters related to adsorption capacity and adsorption strength.…”
Section: Freundlich Modelmentioning
confidence: 99%
“…[1,2] The resulting types of pollutants are also increasing, such as volatile organic compounds, dyes and other organic pollutants produced by various industries, like chemical industry, textile industry and pharmaceutical industry. [3][4][5][6] Most of these pollutants are irritant and toxic, posing a serious threat to human life and ecological environment. Therefore, it is very necessary to develop new materials and methods to effectively reduce or remove these organic pollutants.…”
Section: Introductionmentioning
confidence: 99%